SMART BLUETOOTH AND VOICE CONTROL CAR - Mr.M.RAMANA REDDY , Mrs.N.SWARUPA RANI , NETTURI SAI DINESH , SURE SUBHASH , KANIGIRI PAVAN KUMAR, VADLAMUDI VENKATA RAMANA (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This paper was developed in a way that the car is controlled by voice commands. An android applicationwith a microcontroller is used for required tasks. The connection between the android app and thevehicle is facilitated with Bluetooth technology. The car control by buttons on the application or byspoken commands of the user. The future advancement in this technology will help us in for thehandicapped ones who cannot drive the vehicle on their own, transportation purposes,